Discordance of COVID‐19 guidelines for patients with cancer: A systematic review - Garg, Pankaj Kumar (J Surg Oncol, 2020)
This review was aimed to systematically evaluate the available literature on the impact of COVID‐19 on cancer care and to critically analyze the diagnostic and therapeutic strategies suggested by various healthcare providers, societies, and institutions. Majority guidelines for various types of cancers favored a delay in treatment or a nonsurgical approach wherever feasible. These guidelines are based on a low level of evidence and have significant discordance for the role and timing of surgery, especially in early tumors.